Evaluation of the mutant selection window of danofloxacin against Actinobacillus pleuropneumoniae in an in vitro dynamic model - Zhang, Longfei; Wang, Hongjuan; Bai, Yilin; Wang, Lei; Bai, Yueyu; Hu, Jianhe (Frontiers in Veterinary Science, 2023)
Introduction The rapid emergence and widespread spread of multidrug-resistant bacteria is a serious threat to the health of humans and animals. The pharmacokinetic/pharmacodynamic (PK/PD) integration model based on mutant selection window (MSW) theory is an important method to optimize the dosage regimen to prevent the emergence and spread of drug-resistant bacteria. Actinobacillus pleuropneumoniae (AP) is a pathogen that can cause pleuropneumonia in pigs. Methods We employed an in vitro dynamic infection model (DIM) to study the prevention of drug-resistant mutations of danofloxacin against AP. A peristaltic pump was applied to establish an in vitro DIM to simulate the PK of danofloxacin in plasma, and to study the MSW of danofloxacin against AP. A peristaltic-pump in vitro infection model was established to simulate dynamic changes in the danofloxacin concentration in pig plasma. PK and PD data were obtained. Then, the relationship between PK/PD parameters and antibacterial activity was analyzed by the sigmoid Emax model. Results and discussion The area under the curve during 24 h/ the minimum concentration that inhibits colony formation by 99% (AUC24h/MIC99) had the best-fitting relationship with antibacterial activity. The AUC24h/MIC99 values for a bacteriostatic effect, bactericidal effect, and eradication effect were 2.68, 33.67, and 71.58 h, respectively. We hope these results can provide valuable guidance when using danofloxacin to treat AP infection.